Association between the anatomical profile and the severity of Obstructive Sleep Apnea in a sample of Peruvian patients.: Asociación entre el perfil anatómico y la severidad del Apnea Obstructiva del Sueño en una muestra de pacientes peruanos. - Quispe Sapacayo, Wendy E. (2022)
Introduction:  Obstructive Sleep Apnea (OSA) is the total or partial limitation of the passage of air through the upper respiratory tract during sleep, it has two forms of presentation: central and obstructive (related to anatomical profile). Objective: To determine the relationship between the anatomical profile and severity of Obstructive Sleep Apnea in adult patients of a Private Clinic in Lima Norte, Lima, 2020-2022. Methods:  Cross-sectional analytical study. We used medical records of patients diagnosed with OSA during the period 2020-2022 in a private clinic in Lima, Peru. Our variable was the severity of OSA, in addition to apnea-hypopnea per hour (AHI), in addition we also took oxygen desaturation index (ODI), Epworth Scale, CT90%, body mass index (BMI), minimum saturation and snoring and of the newborn reported in the clinical history. The response variable was OSA . Results: a total of 120 clinical histories were studied. The predominant OSA was mild (29.2%), followed by very severe (26.7%). In very severe OSA, patients with retrognathia had 3.0 higher frequency, those with long face had 30.0 lower frequency and those with short face had 4.0 higher frequency, compared to patients with normal face (40 vs 7 vs 41 vs 37; p<0.01). Conclusions: OSA is associated with the anatomical profile. The ANGLE scale was the one most associated with OSA compared to the Friedman Score. OSA was associated with BMI, IDO, minimum saturation, and maximum heart rate.